Teaching Assistants becoming Primary School Teachers: Changing Professional Identities in communities of practice - Geeson, Rebecca (2022)
This study explores the way that teacher identity is developed in teaching assistants (TAs) who train to teach, and the impact that being part of a community of practice has on this transition. The participants in this research were studying for a top-up degree which included recommendation for qualified teacher status (QTS) while they continued to work as TAs. A narrative inquiry approach was used to foreground the often overlooked voice of the TA in educational research. Findings showed that schools deployed TAs in a wide variety of ways, and this seemed to depend on individual skills and expertise of TAs, and on individual TA-teacher partnerships. However, it was also seen that despite recommendations from the seminal DISS report (Blatchford et al., 2009) and subsequent work by this team, schools do not always follow the recommendations made. The findings of this study also shows that membership of a community of practice (Wenger, 1998) supports TAs in their practice. Relationships within the community of practice are of particular significance in their transition to becoming a teacher. I argue here that TAs and teachers can be seen to have a distinct ‘teaching identity’ rather than having to adopt either a teacher or a TA identity. This study finds that the experience TAs gain as members of a school community of practice while working in the fuzzy liminal space between teacher and TA can support TAs who choose to train as teachers.